Optimizing iron adequacy and absorption to prevent iron deficiency anemia: The role of combination of fortified iron and vitamin C - W. Basrowi, Ray; Dilantika, Charisma (Indonesian Nutrition Association, 2021)
Iron is a vital nutrient to promote the availability of tissue oxygen, cell growth and control of differentiation, and energy metabolism. Preventing Iron Deficiency Anemia (IDA) is necessary because iron is vital to central nervous system growth and development especially in the first years of life. Iron-rich complementary foods are recommended in infants around 6 months of age because iron store is depleted. Better understanding of iron absorption process and factors affecting its absorption and bioavailability is necessary to prevent iron deficiency and can be a dietary strategy to mitigate iron deficiency. Meat and iron-fortified food are the main sources of iron in the diet, and it is essential to introduce supplementary food to improve iron absorption. Additional foods such as cereals, cow milk and soybeans such as phytate, polyphenol and calcium are inhibitors which require care to prevent IDA. Ascorbic acid is an effective iron-absorbing enhancer, which is useful to reduce the effects of any known nonheme iron inhibitor. In iron-fortified foods, Combination use of vitamin C (ascorbic acid) is recommended in molar ratio of 2:1 (with cow's milk and low-phytate cereal foods) and higher molar ratio of 4:1 (with higher phytate such as soybeans).